Small molecules targeting the inactive form of the Mnk1/2 kinases - Kannan, Srinivasaraghavan (2021)
Overexpression of the eukaryotic initiation factor 4E (eIF4E) is linked to a variety of cancers. Both mitogen-activated protein kinases-interacting kinases 1 and 2 (Mnk1/2) activate the oncogene eIF4E through posttranslational modification (phosphorylating it at the conserved Ser209). Inhibition of Mnk prevents eIF4E phosphorylation, making the Mnk-eIF4E axis a potential therapeutic target for oncology. Recently, the design and synthesis of a series of novel potent compounds inhibiting the Mnk1/2 kinases were carried out in-house. Here, we describe computational models of the interactions between Mnk1/2 kinases and these inhibitors. Molecular modeling combined with free energy calculations show that these compounds bind to the inactive forms of the kinases. All compounds adopt similar conformations in the catalytic sites of both kinases, stabilized by hydrogen bonds with the hinge regions and with the catalytic Lys78 (Mnk1) and Lys113 (Mnk2). These hydrogen bond interactions clearly play a critical role in determining the conformational stability and potency of the compounds. We also find that van der Waals interactions with an allosteric pocket are key to their binding and potency. Two distinct hydration sites that appear to further stabilize the ligand binding/interactions were observed. Critically, the inclusion of explicit water molecules in the calculations results in improving the agreement between calculated and experimental binding free energies.